SINTESIS SENYAWA ISOFLAVON DARI MINYAK DAUN CENGKEH DAN UJI AKTIVITAS ANTIKANKER SECARA IN VITRO - , ANDI HAIRIL ALIMUDDIN ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Synthesis of isoflavone derivatives from eugenol, isolated from clove leaves oil, had been conducted. Firstly, eugenol was converted into 3,4-dimethoxybenzyl carboxylate and 3,4-dimethoxybenzyl cyanide. The two compounds were then condensed with phenolic compounds to produce isoflavone. The synthesized isoflavones were used in in vitro anticancer assay against T47D cancer cell line. Synthesis of 3,4-dimethoxybenzyl carboxylate was conducted in two ways: oxidation of methyleugenol using KMnO4 (21% yield) and hydrolysis of benzyl cyanide using H2SO4 65% (85% yield). 3,4-Dimethoxybenzyl cyanide was obtained from eugenol via several steps. Methylation of eugenol using DMS gave methyleugenol (89,78%), which was then isomerized using t-BuOK in DMSO to give methyl isoeugenol (85,7%). The isomerization product was oxidized with KMnO4 to produce 3,4-dimethoxybenzaldehyde (85,45%). The aldehyde was reduced by NaBH4 (98,21%), followed by substitution using SOCl2 to yield 3,4- dimethoxybenzyl chloride. Nitrilization of the previous product using NaCN produced 3,4-dimethoxybenzylcyanide (89.5%). Then, Friedel-Crafts acylation between 3,4-dimethoxybenzylcarboxylate and resorcinol in the presence of BF3- Et2O yielded 3,4-dimethoxbenzyl-2',4'-dihydroxyphenyl ketone in 76% yield. In addition, the benzyl cyanide derivative was reacted with phloroglucinol to afford 3,4-dimethoxybenzyl-2',4',6'-trihydroxyphenyl ketone in 56% yield, based on Houben-Hoesch reaction. Isoflavones of 7-hydroxy-3',4'-dimethoxyisoflavone and 5,7-dihydroxy-3',4'-dimethoxisoflavone were obtained from the benzyl- and phenyl ketones in 84% and 83% yields, respectively, using the reagent of BF3- Et2O/DMF/benzene suphonyl chloride. Derivatization of 7-hydroxy-3',4'- dimethoxyisoflavones using reagents of benzyl chloride, benzoyl chloride, acetyl chloride, ethyl-2-chloroacetate and DMS produced 7-O-benzyl- (80.9% yield), 7- O-benzoyl- (83.7% yield), 7-O-acetyl- (78.2% yield), 7-O-ethoxycarbonylmethyl- (74.5% yield) and 7,3â,4â-trimethoxyisoflavone (78,9%). Furthermore, derivatization of 5,7-hydroxy 3â,4â-dimethoxyisoflavones produced 7-Oethoxycarbonylmethyl- (72.4% yield), 7-O-carboxylmethyl- (93,4%), 5,7-Odibenzoyl- (82.5% yield) and 7-O-acetyl- (75.4% yield). The citotoxic test of the synthesized isoflavones to cancer cell of T47D showed that all isoflavones had IC50 higher than100 Î¼g/mL. The isoflavones, in fact, did not display anticancer activity to T47D cancer cell line.